THE EFFECT OF THE IMAGE EXPLANATION TEACHING TECHNIQUE TO IMPROVE THE SPEAKING ABILITY OF THE SEVENTH-GRADE STUDENTS OF THE MTs NAHDLATUL MUJAHIDIN NW JEMPONG IN ACADEMIC YEAR 2023/2024 - rabiatun aulia (Journal of English Education and Literature, 2024)
The students just gave a little response when they were asked in English (low participant). This research aims to determine the effect of using the image explanation technique on the speaking ability of seventh-grade students of the MTs Nahdlatul Mujahidin NW Jempong. This type of research is Experimental Research ( Quantitative Approach ). This research design uses a Pre-Test and Post-Test design. The population of this study was all seventh-grade students. This research sample namely VII-A as an Experimental Class with 20 students and VII-B as an Control Class with 20 students. The results of the Experimental Class analysis show that the mean Pre-Test score in Experimental Class is 36.99 and the mean Post-Test score is 81.66. Meanwhile, the results of the Control Class analysis show that the mean Pre-Test score in Control Class is 36.99 and the mean Post-Test score is 58.99. This shows that the Experimental Class experienced an increase in their speaking test, and hypothesis testing showed that the Experimental Class students’ scores were higher than those in the Control Class. The instrument used in this research was the Speaking Test. The technique used to analyze data is the t-test. The results of the independent sample t-test show a significance value (2-tailed) of less than 0.05 (<0.05). This means the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Based on the research results, it was concluded that the image explanation method had a positive effect on improving students’ speaking skills in English.